Novel : Holo Meta Bolus and Mini-dissertation : “Sal jy my verstaan?” : The representation of post-apartheid Afrikaner repudiation in Fokofpolisiekar lyrics. - Medalie, David (University of Pretoria, 2022)
Dissertation (MA (Creative Writing))--University of Pretoria, 2021.